Artificial Intelligence in the Sphere of Security - Gaie, Christophe; Karpiuk, Mirosław; Melchior, Claudio (Studia Iuridica Toruniensia, 2026)
Nowadays, artificial intelligence is used in various spheres of life, including state operations. Security is one of such domains. New technologies should be used universally across the entire sphere of security. This also applies to artificial intelligence which allows us not only to respond to existing threats but also to anticipate and prevent them (i.a., through the analysis of large data sets over a short time). However, artificial intelligence should be applied in a responsible manner, so that its use does not constitute threats to security but rather contributes to its protection. The objective of this paper is to analyze the possibility to apply artificial intelligence in the security environment that needs to be open to new solutions, so that it is possible to protect our societies and states more effectively than at present. The author’s thesis can be expressed in the statement that artificial intelligence may contribute to security enhancement, provided that it is used responsibly and is properly supervised. This paper is based on the doctrinal legal research method and the law theory method.